Formulation and Evaluation of Nanoemulsion Gel of Tenoxicam For Topical Application - Sharma, Pawan; Namdev, Abhisek; Agrawal, Dilip; Khinchi, Mahaveer; Soni, Shankar (Asian Journal of Pharmaceutical Research and Development, 2015)
The aim of the present study to develop a nanoemulsion gel formulation of poorly water soluble drug tenoxicam for the transdermal delivery. Nanoemulsions have the particle size range in nano range. Particle size in nanoemulsion formulation determines the stability of formulation so it’s very important to achieve the optimum size of particles to formulate the drug. To develop the nanoemulsion here ethyl oleate, tween-80 and propylene glycol were selected among various types of oils, surfactants and co-surfactants for preparing nanoemulsion. Various oil-in-water nanoemulsions were prepared by the spontaneous emulsification method. The nanoemulsion area was identified by constructing ternary phase diagrams. The prepared nanoemulsions were subjected to different thermodynamic stability tests to screen out the stable formulations among various prepared formulation having different smix ratios with oil phase. The Tenoxicam containing nanoemulsion gel was prepared and characterized for particle size, zeta potential, pH, In-vitro drug release and viscosity. Tenoxicam nanoemulsion gel treated dyliasis membrane employed to investigate the skin permeation mechanism of tenoxicam from nanoemulsion gel. The obtained results from the study suggested that nanoemulsions are potential vehicles for improved transdermal delivery of Tenoxicam.